EFFECT OF INTRAVENOUS ADMINISTRATION OF SECRETOME ON MALONDIALDEHYDE LEVELS IN ROTENONE-INDUCED PARKINSON'S DISEASE RATS - Aliza, Sharla; Sidharta, Veronika Maria; Sasmita, Poppy Kristina; Ardianto, Christian; Barus, Jimmy (MNJ (Malang Neurology Journal), 2025)
Background: Parkinson's disease (PD) is a progressive neurodegenerative disorder with an increasing prevalence. Oxidative stress is known to contribute to the development of PD through lipid peroxidation, which causes damage to the substantia nigra pars compacta. Lipid peroxidation produces malondialdehyde (MDA), which is known to be elevated in PD patients. Up till now, there is no cure for PD, and the available therapies are only symptomatic. The secretome from Mesenchymal Stem Cell (MSC) has antioxidant and neuroprotective components, making it a potential therapeutic agent that may slow the progression of PD. Objective: This study seeks to determine the effect of MSC secretome on oxidative stress in rotenone-induced PD rats. Methods: This research was an in-vivo experiment conducted with 30 male Sprague Dawley rats, divided into sham control, rotenone (+) secretome (-), and rotenone (+) secretome (+) groups. Rotenone (2.75 mg/kgBW) was administered for seven days to induce a PD model. Secretome administration (1 mg/ml) was carried out on days 3, 5, and 7. MDA levels were determined using the sandwich ELISA method. Results: This study found no significant difference in MDA levels among the three groups (p = 0.203). The sham control group had the lowest MDA 1.32(0.53) nmol/mL, followed by the rotenone (+) secretome (+) group 1.56(0.33) nmol/ml, and the highest MDA was observed in the rotenone (+) secretome (-) group 1.88(0.14) nmol/mL. Conclusion: Administration of MSC secretome did not significantly cause changes in plasma MDA levels of rotenone-induced Parkinson Disease rats.